2010
DOI: 10.1108/14502191011065491
|View full text |Cite
|
Sign up to set email alerts
|

Green marketing

Abstract: Purpose-The purpose of this paper is to study the possibility of promoting certified timber coming from sustainable managed forests, in order to support Greek enterprises and the institutions of the Greek timber sector involved to apply effective green marketing methods and policies. Design/methodology/approach-Based on a prototype questionnaire, specifically structured for the aim of the research, 55 responses were collected from Greek timber enterprises in April 2009. The questionnaires were processed and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…foil, plastics etc. ), logistical convenience driven by consumer green values remains at the core of this study (Lin and Ho 2008;Papadopoulos et al 2010;Kanonuhwa and Chimucheka 2014). This activity might even be interpreted by some as another dimension of collaboration, towards a more closed loop business approach (Linton 2005;Kraaijenhagen, van Oppen and Bocken 2016), along the coffee value chain.…”
Section: Designing a Research Frameworkmentioning
confidence: 89%
See 2 more Smart Citations
“…foil, plastics etc. ), logistical convenience driven by consumer green values remains at the core of this study (Lin and Ho 2008;Papadopoulos et al 2010;Kanonuhwa and Chimucheka 2014). This activity might even be interpreted by some as another dimension of collaboration, towards a more closed loop business approach (Linton 2005;Kraaijenhagen, van Oppen and Bocken 2016), along the coffee value chain.…”
Section: Designing a Research Frameworkmentioning
confidence: 89%
“…Existing commentary about this new way of coffee drinking usually refers to: consumer demand, successful market strategies and product management. This paper locates the argument within important discussions about circular economy and the growing green awareness of customers (Lin and Ho 2008;Papadopoulos et al 2010;Kanonuhwa and Chimucheka 2014). It provides a viable argument for resource preservation and resource recovery within the coffee drinking value chain, based on the commitment of Brazilians to ethical enterprise.…”
Section: Final Remarks and Future Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, improved market access and wood products' quality are gained through sustainably managed forests that are derived from this initiative (Siry et al 2005). Increasing demand for green labelling of products has been observed, which is termed 'green marketing' through green certification (Vlosky et al 1999;Aguilar and Cai 2010;Papadopoulos et al 2010). Kollert and Lagan (2007) showed that certified logs achieved market premium compared to uncertified logs that only reach a lower market premium price.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, all the nations across the globe are worrying about environmental problems namely global warming, environmental pollution and degradation, climate change and depletion of environmental resources (Atthirawong and Panprung, 2017). Nowadays, consumers are also having higher degree of apprehension on changes in environment in comparison with past years and their purchasing behaviour are also remarkably changed (Papadopoulos et al 2010). Consumers are giving importance to environmental problems in purchasing and consuming various products (Hessami and Yousefi, 2013).…”
Section: Introductionmentioning
confidence: 99%